Subscribed why the subscription model will be your company's future - and what to do about it - Tzuo, Tien; Weisert, Gabe (Portfolio/Penguin, 2018)
"Companies like Netflix, Spotify, and Salesforce are just the tip of the iceberg for the subscription model. The real transformation...and the real opportunity...is just beginning"...